2020
DOI: 10.1038/s41467-020-16500-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into the electron transfer pathway of a self-sufficient P450 monooxygenase

Abstract: Cytochrome P450 monooxygenases are versatile heme-thiolate enzymes that catalyze a wide range of reactions. Self-sufficient cytochrome P450 enzymes contain the redox partners in a single polypeptide chain. Here, we present the crystal structure of full-length CYP116B46, a self-sufficient P450. The continuous polypeptide chain comprises three functional domains, which align well with the direction of electrons traveling from FMN to the heme through the [2Fe-2S] cluster. FMN and the [2Fe-2S] cluster are position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…In both of these cases, the P450 domain was substrate-bound. The most recently reported structure of a self-sufficient P450 monooxygenase CYP116B46 (a P450-reductase-ferredoxin in one polypeptide chain), although outlining the interaction between the FMN of the reductase domain and the Fe-S cluster of the ferredoxin domain, does not clearly reveal the productive interaction between the ferredoxin and the P450 domains ( Zhang et al. 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In both of these cases, the P450 domain was substrate-bound. The most recently reported structure of a self-sufficient P450 monooxygenase CYP116B46 (a P450-reductase-ferredoxin in one polypeptide chain), although outlining the interaction between the FMN of the reductase domain and the Fe-S cluster of the ferredoxin domain, does not clearly reveal the productive interaction between the ferredoxin and the P450 domains ( Zhang et al. 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structures of OhpA homologues from A. radioresistens S13 and Tepidiphilus thermophiles JCM 19170 have been recently solved, providing first bases for the structure‐guided design of new biocatalysts with these enzymes (Tavanti et al ., 2018; Ciaramella et al ., 2019; Zhang et al ., 2020). According to the X‐ray structure of the homologue harboured by strain JCM 19170, it was revealed that the catalytic pocket of the enzyme is surrounded by 18 residues organized in a 4‐tiered system above the haem cofactor that are well conserved among CYP116B members (Tavanti et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Zhang et al report the CYP116B46 full-length crystal structure solved at 2.13 Å, which produces a detailed picture of the multi-domain arrangement as well as the electron tunneling architecture of class VII P450s. [76] The primary sequence suggests a domain alignment from N to C terminus to be P450, FMNcontaining reductase domain and [2Fe-2S]-containing domain. The structure shows that [2Fe-2S]-containing domain is located in between the two other domains (Figure 5A).…”
Section: Cyp116b46mentioning
confidence: 99%
“…To probe this issue, the study examined the catalytic activity of CYP116B46 variants in which several polar residues located between [2Fe‐2S] and heme are mutated to Ala. The results indicate that several polar residues play a role in enzyme activity [76] (Figure 5B). In fact, long‐range ET is prevalent in many biological events such as photosynthesis and aerobic respiration [78] .…”
Section: The Electron‐transfer Mechanism Of Self‐sufficient P450smentioning
confidence: 99%